2019–2020 Florida Citrus Production Guide: Exocortis, Cachexia, and Other Viroids - Ozgur Batuman; Amit Levy; Ronald H. Brlansky (EDIS, 2019)
Exocortis and cachexia are diseases caused by viroids, which can lead to stunted growth and reduced yields in affected plants. Viroids are small, infectious circular-RNA molecules. Exocortis causes dwarfing and bark scaling on rootstocks such as trifoliate orange and many of its hybrids such as Carrizo citrange, Rangpur lime, and others. This 2-page fact sheet is part of the 2019–2020 Florida Citrus Production Guide. Written by Ozgur Batuman, Amit Levy, and Ronald H. Brlansky, and published by the Plant Pathology Department, March 2019.